Multi-Ethnic Students in Malaysia Higher Institutions: Relationship between Racial Integration and Democratic Outcomes - Majid, Noraziela Abdul; Hassan, Aminuddin; Hassan, Norlizah Che (International Journal of Psychosocial Rehabilitation, 2020)
This paper is a conceptual paper in which it studies multi-ethnic students in Malaysia higher institutions, in the context of the relationship between racial integration and democratic outcomes. Malaysia is made up from a variety of ethnic groups with their own uniqueness and heritage such as language, traditions and beliefs. So, Malaysians are definitely aware of this fact and therefore all citizens regardless of their background need to unite in order for the country's progress to be achieved without hindrance. Thus, one of the ways to ensure that national security is maintained among the multicultural people is through education. However, the school system in Malaysia that has segregated students since the elementary school or known as primary school level has caused students of different ethnic backgrounds to be a part of each other, leading to very limited interactions among them and added to the issue of democratic outcomes of the students as well. Henceforth, this study aimed to determine racial integration with democratic outcomes among students of various ethnicities in Malaysian Institutions of Higher Learning. In addition, this research also wanted to study the effect social interaction as a mediating factor between these students. To obtain the best results for this study, quantitative methods supported by several open-ended questions will be used. By using convenience sampling techniques, a total of 400 questionnaires will be distributed to respondents. Then through descriptive and inferential statistics, all data collected will be analyzed using the Statistical Package for Social Science (SPSS) latest version program. Then, for the purpose of answering the research questions of this research, Pearson Coefficient (r) and Structural Equation Modeling (SEM) will be applied.